Fetal cardiac dimensions at 14-40 weeks' gestation obtained using cardio-STIC-M - Luewan S. (2017)
Objectives To establish normative reference ranges of fetal cardiac dimensions derived from volume datasets acquired using spatiotemporal image correlation with M-mode display (cardio-STIC-M). Methods A cross-sectional study was undertaken on singleton pregnancies with normal fetuses and accurate gestational ages. Cardio-STIC volume datasets were acquired by experienced operators using a high-resolution ultrasound machine; these were maneuvered to obtain a four chamber-view with exactly horizontal interventricular septum (IVS). Cardiac dimensions were measured in STIC-M-mode using 4D View software. Results A total of 657 measurements, at a rate of between 15 and 37 per week, were obtained. Normal reference ranges for biventricular outer diameter, left and right ventricular inner diameter, left and right ventricular wall thickness, IVS thickness, left to right ventricular diameter ratio and left and right ventricular shortening fractions were constructed based on best-fit equations as a function of gestational age, fetal head circumference and biparietal diameter. Thirty-four volume datasets of abnormal fetal hearts were also separately assessed, many of which showed abnormal cardiac dimensions. Conclusions This is the first report on normal ranges of fetal cardiac dimensions constructed using the new cardio-STIC-M technology. Preliminary evaluation suggests that these reference ranges may be a useful tool in the assessment of fetal cardiac abnormalities. © 2011 ISUOG. Published by John Wiley & Sons, Ltd.